Core–Shell Imidazoline–Functionalized Mesoporous Silica Superparamagnetic Hybrid Nanoparticles as a Potential Theranostic Agent for Controlled Delivery of Platinum(II) Compound - Abedi M (Dove Medical Press, 2020)
Mehdi Abedi,1 Samira Sadat Abolmaali,1,2 Mozhgan Abedanzadeh,1 Fatemeh Farjadian,2 Soliman Mohammadi Samani,2,3 Ali Mohammad Tamaddon1,2 1Department of Pharmaceutical Nanotechnology, School of Pharmacy, Shiraz University of Medical Sciences, Shiraz, Fars, Iran; 2Center for Nanotechnology in Drug Delivery, School of Pharmacy, Shiraz University of Medical Sciences, Shiraz, Fars, Iran; 3Department of Pharmaceutics, School of Pharmacy, Shiraz University of Medical Sciences, Shiraz, Fars, IranCorrespondence: Ali Mohammad TamaddonDepartment of Pharmaceutical Nanotechnology, School of Pharmacy, Shiraz University of Medical Sciences, Shiraz, Fars, IranTel +98 71 32424126Email amtamadon@gmail.comIntroduction: As widely used chemotherapeutic agents, platinum compounds have several therapeutic challenges, such as drug resistance and adverse effects. Theranostic systems, macromolecular or colloidal therapeutics with companion diagnostics, not only address controlled drug delivery but also enable real-time monitoring of tumor sites.Methods: Synthesis of magnetic mesoporous silica nanoparticles (MMSNs) was performed for dual magnetic resonance imaging and drug delivery. MMSN surfaces were modified by imidazoline groups (MMSN-Imi) for cisplatin (Cis-Pt) conjugation via free N-termini to achieve well-controlled drug-release kinetics. Cis-Pt adsorption isotherms and drug-release profile at pH 5 and 7.4 were investigated using inductively coupled plasma atomic emission spectroscopy.Results: MMSN-Imi showed a specific surface area of  517.6 m2 g− 1, mean pore diameter of  3.26 nm, and saturated magnetization of 53.63 emu/g. A relatively high r2/r1 relaxivity value was obtained for MMSN-Imi. The nanoparticles provided high Cis-Pt loading with acceptable loading capacity (∼ 30% w:w). Sustained release of Cis-Pt under acidic conditions led to specific inhibitory effects on the growth of human epithelial ovarian carcinoma cells, determined using MTT assays. Dual acridine orange–propidium iodide staining was investigated, confirming induction of apoptosis and necrotic cell death.Conclusion: MMSN-Imi exhibited potential for applications in cancer chemotherapy and combined imaging.Keywords: magnetic properties, cisplatin, SiO2, theranostic, MRI, drug delivery